3-Ethenyl-1-(4-methylphenylsulfonyl)-1H-indole - Zukerman-Schpector, Julio; Wulf, Glaudeston D.; Stefani, Hélio A.; Vasconcelos, Stanley N.S.; Ng, Seik Weng; Tiekink, Edward R.T. (International Union of Crystallography, 2012)
Two independent but very similar molecules comprise the asymmetric unit of the title compound, C17H15NO2S. The molecules have L-shapes with the dihedral angles between the fused-ring system (r.m.s. deviations = 0.036 and 0.019 Å, respectively) and the benzene ring being almost the same, i.e. 82.98 (12) and 84.46 (13)°, respectively. The terminal ethenyl group is almost coplanar with the ring to which it is connected [C - C - C - C torsion angles = -173.7 (4) and -171.7 (4)°, respectively]. Supramolecular arrays parallel to (1̄24) stabilized by C - H⋯O and C - H⋯π interactions feature in the crystal packing.